GE_GERICHTE C/22552/2016 vom 24. April 2017 - GE Cour de justice (2017)
BAIL À LOYER ; EXPULSION DE LOCATAIRE ; CAS CLAIR ; IMMUNITÉ ; PROLONGATION DU BAIL À LOYER ; PROPORTIONNALITÉ | CPC.257; LEH.2, 3, 26; CVRD.31.1, 39.2; OLEH.9,15; LaCC.30.4;